Practical Guide to Project Planning - Vargas, Ricardo Viana (CRC Press, 2009)
Practical Guide to Project Planning is filled with project documents and templates ready to use for planning and managing project. It explains project analysis and modeling techniques so these documents and templates can be used for effective project management. In addition, the book is also a guide to best practices that comply with the PMI’s PMBOK ® 3.0.